2006
DOI: 10.1590/s1806-37132006000300003
|View full text |Cite
|
Sign up to set email alerts
|

Adesão às medidas de controle ambiental em lares de crianças e adolescentes asmáticos

Abstract: Objective: To determine, through home visits, the rate of compliance with environmental control measures in the homes of children with asthma. Methods: This study involved 98 asthma patients between the ages of 4 and 15. The parents of those children and adolescents received instruction in how to carry out environmental control measures and were encouraged to perform such measures continuously for a period of 90 days. Home visits, which included direct inspection of the domicile and administration of a questio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 21 publications
0
1
0
1
Order By: Relevance
“…Awareness of symptoms, education on therapy, cultural and societal factors affect a patient's perspective and treatment adherence. Among children of different Latino ethnicities, girls from low-income families had poorer adherence to ICS over a 12month period [34,35] and Jentzsch et al [36] showed that compliance to recommendations to reduce or minimize allergen and/or trigger factor exposure was achieved in less than 9.2% of patients among low-income families in rural Brazil. The Covid-19 pandemic of 2020 has highlighted the important role of knowledge, science and education in effecting an appropriate response to any healthcare threat.…”
Section: The Role Of Education and Literacy/learning Povertymentioning
confidence: 99%
“…Awareness of symptoms, education on therapy, cultural and societal factors affect a patient's perspective and treatment adherence. Among children of different Latino ethnicities, girls from low-income families had poorer adherence to ICS over a 12month period [34,35] and Jentzsch et al [36] showed that compliance to recommendations to reduce or minimize allergen and/or trigger factor exposure was achieved in less than 9.2% of patients among low-income families in rural Brazil. The Covid-19 pandemic of 2020 has highlighted the important role of knowledge, science and education in effecting an appropriate response to any healthcare threat.…”
Section: The Role Of Education and Literacy/learning Povertymentioning
confidence: 99%
“…As crianças e adolescentes do estudo expostas à poeira doméstica e animais de estimação apresentaram maior chance de apresentar asma não controlada e grave. A exposição à aeroalérgenos aumenta o risco da exacerbação da asma, e a profilaxia ambiental melhora o controle e a gravidade da doença, assim, torna-se importante reforçar tanto para o paciente, quanto para a sua família sobre a necessidade de afastar os asmáticos dos possíveis fatores desencadeantes da crise 1,28,[116][117][118] . A média de crises do último ano e nos últimos três meses, segundo o controle foi maior nos pacientes do Grupo ANC e segundo a gravidade no Grupo AG.…”
Section: Sintomasunclassified